Nafion-stabilised bimetallic Pt–Cr nanoparticles as electrocatalysts for proton exchange membrane fuel cells (PEMFCs). Issue 86 (1st September 2016) - Gupta, G.; Sharma, S.; Mendes, P. M.
Abstract : The current study investigated the unique combination of alloying (Pt with Cr) and Nafion stabilisation to reap the benefits of catalyst systems with enhanced catalytic activity and improved durability in PEMFCs. Abstract : The current study investigated the unique combination of alloying (Pt with Cr) and Nafion stabilisation to reap the benefits of catalyst systems with enhanced catalytic activity and improved durability in PEMFCs. Pt–Cr alloy nanoparticles stabilised with Nafion were chosen in the current study owing to their higher stability in acidic and oxidising media at high temperatures compared to other Pt-transition metal alloys ( e.g. Pt–Ni, Pt–Co). Two different precursor : reducing agent (1 : 10 and 1 : 20) ratios were used in order to prepare two different alloys, denoted as Pt–Cr 10 and Pt–Cr 20. The Pt–Cr 20 alloy system (with composition Pt80 Cr20 ) demonstrated higher electrocatalytic activity for the oxygen reduction reaction compared to commercial Pt/C (TKK) catalysts. Accelerated stress tests and single cell tests revealed that Nafion stabilised alloy catalyst systems displayed significantly enhanced durability (only ∼20% loss of ECSA) compared with Pt/C (50% loss of ECSA) due to improved catalyst–ionomer interaction. Furthermore, the Pt–Cr 20 alloy system demonstrated a current density comparable to that of Pt/C making them promising potential electrocatalysts for proton exchange membrane fuel cells.